2019
DOI: 10.1111/hae.13861
|View full text |Cite
|
Sign up to set email alerts
|

Concizumab promotes haemostasis via a tissue factor‐factor VIIa–dependent mechanism supporting prophylactic treatment of haemophilia: Results from a rabbit haemophilia bleeding model

Abstract: In recent years, the development of novel therapeutic agents for haemophilia has focused on molecules allowing subcutaneous and/ or less frequent administration compared with intravenous factor replacement therapies in order to improve adherence and compliance and, ultimately, long-term outcomes. Concizumab (Novo Nordisk A/S) is a novel agent currently in phase 2 clinical development as a subcutaneous treatment for the prevention of bleeding episodes, including long-term prophylaxis, in patients with haemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Lauritzen & Hilden in their letter to editor, recently published, 13 described three independent studies performed on hemophilic rabbits. These studies confirmed previous data: escalating doses of concizumab administered within five minutes from cuticle bleeding induction are equally effective to reduce the ongoing bleeds, but concizumab resulted less effective than rFVIIa if administered 15–30 minutes after bleeding induction.…”
Section: Resultsmentioning
confidence: 99%
“…Lauritzen & Hilden in their letter to editor, recently published, 13 described three independent studies performed on hemophilic rabbits. These studies confirmed previous data: escalating doses of concizumab administered within five minutes from cuticle bleeding induction are equally effective to reduce the ongoing bleeds, but concizumab resulted less effective than rFVIIa if administered 15–30 minutes after bleeding induction.…”
Section: Resultsmentioning
confidence: 99%